FACTOR ANALYSIS OF SPECIAL PHYSICAL PREPAREDNESS OF GYMNASTS AGED 8–10 - Bermudes, D. V.; Balashov, D. I.; Stasenko, O. A. (Rehabilitation and Recreation, 2024)
The article highlights that the technical preparedness of gymnasts is based on special physical preparedness and serves as a crucial benchmark for pedagogically justified modeling of educational and training processes. The aim of the research is to determine the indicators of development of special physical preparedness among gymnasts aged 8–10 and its factorial structure. Materials and Methods. Pedagogical testing of special physical preparedness among gymnasts aged 8–10 was conducted in the city of Sumy. Children’s and youth sports schools were chosen as the research bases. The pedagogical experiment involved 57 male gymnasts aged 8–10. Pedagogical tests were selected, and factor analysis was applied to determine the factors of special physical preparedness of gymnasts in each age group. Results. The research results demonstrate that the special physical preparedness of 8-year-old gymnasts depends by 35.8% on the level of development of strength endurance, by 14.9% on flexibility development, and 10.3% is determined by speed-strength preparedness. Analysis of indicators of special physical preparedness among 9-year-old gymnasts revealed that it is determined by the level of maximal strength development (32.7%), flexibility (10.9%), the quality of strength endurance development (8.0%), and by 6.5% is defined by the manifestation of maximal strength capabilities in a minimal period of time (explosive strength). The research results revealed that the specific physical preparedness of 10-year-old gymnasts depends on 33.2% of the ability to demonstrate maximum strength, 17.4% on the level of flexibility development, and 10.2% is determined by speed-strength. Conclusions. The study of indicators of specific physical preparedness development in gymnasts aged 8–10 and its factorial structure determined that the indicators of specific physical preparedness in gymnasts aged 8, 9, and 10 are not uniform. According to the research results, it can be stated that the specific physical preparedness of gymnasts at the specified age is determined by the level of development of strength endurance, maximum strength, flexibility, and speed-strength qualities. It was determined that the factor of coordination abilities did not manifest in any of the age periods, i.e., it did not enter the list of the first four leading factors. This fact can be explained by the significant volume of exercises studied at the age of 8–10, which does not pose a particularly complex coordination challenge for gymnasts.